Oxygen saturation during the first 24 hours of life. Issue 1 (1st July 2000) - O'Brien, L M; Stebbens, V A; Poets, C F; Heycock, E G; Southall, D P
Abstract : AIM: To determine normative data for arterial oxygen saturation, measured by pulse oximetry (SpO2 ), in healthy full term infants throughout their first 24 hours of life. METHODS: Long term recordings of SpO2, pulse waveform, and breathing movements were made on 90 infants. Recordings were analysed for baseline SpO2, episodes of desaturation (SpO2  ⩽ 80%), apnoeic pauses of ⩾ four seconds, and periodic apnoea (⩾ three apnoeic pauses, each separated by ⩽ 19 breaths). RESULTS: Median baseline SpO2 was 98.3% (range 88.7–100). Longitudinal analysis at four hour intervals showed that SpO2 remained stable until 20–24 hours of age, when it became significantly lower (p < 0.03). Episodic desaturations were identified in 23 recordings. Nine prolonged desaturations (SpO2  ⩽ 80% for ⩾ 20 seconds) were identified in six recordings. Four desaturations fell to ⩽ 60%. Periodic apnoea was identified in 60% of recordings. CONCLUSION: The range of SpO2 during the first 24 hours of life is similar to that found previously during the first month of life. The clinical significance of the prolonged episodes of desaturation observed justifies further investigation.